2007
DOI: 10.1111/j.1445-5994.2007.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture prevention strategies in patients presenting to Australian hospitals with minimal‐trauma fractures: a major treatment gap

Abstract: Most patients presenting to Australian hospitals with minimal-trauma fracture are neither investigated nor treated for osteoporosis. As this group is at high risk of subsequent fracture, this is a missed opportunity to reduce fracture burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 29 publications
7
61
1
1
Order By: Relevance
“…This project study aimed to improve osteoporosis management as directed by the algorithm to 90% and above. Prior to intervention implementation, the treatment and assessment rates were estimated by the research pharmacist to be between 10% and 20%, which compares with previously reported rate of 12% and 10%, respectively [11]. The magnitude of change that the project was aiming to achieve was large, 70-80%.…”
Section: Statistical Assessmentmentioning
confidence: 65%
See 3 more Smart Citations
“…This project study aimed to improve osteoporosis management as directed by the algorithm to 90% and above. Prior to intervention implementation, the treatment and assessment rates were estimated by the research pharmacist to be between 10% and 20%, which compares with previously reported rate of 12% and 10%, respectively [11]. The magnitude of change that the project was aiming to achieve was large, 70-80%.…”
Section: Statistical Assessmentmentioning
confidence: 65%
“…Patients were included in this study if they had been admitted to the orthopaedic ward with a diagnosed minimal trauma fracture where a minimal trauma fracture is defined as a fracture occurring following a fall from standing height or less and excludes fractures of the head and neck and fractures resulting from motor vehicle accidents [11].…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that non-treatment of osteoporosis is common [8][9][10][11][12][13][14][15][16][17][18][19][20] , whether assessed after clinical or self-reported OP diagnosis 10,20 , before OP-related fractures 8,11,16 , or after fractures 9,[11][12][13][14][15][16][17][18][19] . Common barriers to treatment initiation include: concerns over side effects 21 including gastro-intestinal (GI) events [22][23][24][25] , cost 26 , and patient frailty 26 .…”
Section: Introductionmentioning
confidence: 99%